Risk factors of severe dengue in children: A nested case-control study - Sridevi A Naaraayan; Kuthanoor Chinnasamy Sundar (Wolters Kluwer Medknow Publications, 2021)
Background: Dengue is a mosquito-borne viral disease whose severity varies from a mild undifferentiated fever to severe fatal form. The objectives of this study were to determine the prevalence and risk factors of severe dengue. Subjects and Methods: This nested case-control study was done in a medical college hospital in South India from October 2019 to January 2020. Children between 1 month and 12 years of age who presented with fever without focus and tested positive for dengue serology were included. Demographic data, anthropometry, clinical features, and laboratory parameters were noted down from all children. Severity of illness was classified according to the World Health Organization dengue guidelines 2009. Prevalence of severe dengue was expressed in proportion with 95% confidence interval (CI). Bivariate analysis was performed using Chi-square test, Fisher's test, and Student's t-test, and a P < 0.05 was considered statistically significant. Results: Out of 370 children, 192 (51.9%) had dengue without warning signs, 168 (45.4%) had dengue with warning signs, and 10 had severe dengue. The prevalence (95% CI) of severe dengue was 2.7% (1.3%-4.9%). Abdominal pain/tenderness (odd's ratio [OR] - 7.429), facial puffiness (OR - 4.333), hepatomegaly (OR - 3.857), and pleural effusion (OR - 13.222) were the significant risk factors for severe dengue. Conclusions: The significant risk factors for severe dengue were abdominal pain/tenderness, facial puffiness, hepatomegaly, and pleural effusion.